The Effect of the Experimental Method on Natural and Social Sciences Learning Outcomes of Grade IV Students at SDN 1 Watubelah - Yuh May Ilona; Abdul Karim; Sati Sati (FKIP - Universitas Riau, 2026)
Low student achievement in Natural and Social Sciences (IPAS) in the fourth grade at SD Negeri 1 Watubelah. This situation is caused by the teaching methods that have been used so far, namely discussion and the presentation of images. These methods do not provide concrete learning experiences and do not encourage students to participate actively. Consequently, the majority of students have low learning outcomes. The purpose of this study was to determine the effect of the experimental method on the IPAS learning outcomes of fourth-grade students at SDN 1 Watubelah. The research uses a quantitative approach with an experimental method and a pre-experimental design of the one-group pretest-posttest design type. The study population comprises all students at SD Negeri 1 Watubelah, with a sample of 25 fourth grade students. Data collection was conducted through achievement tests, observations, and documentation. The results of the hypothesis test showed that Ho was rejected and Ha was accepted because it produced a significance value of 0.000, which is smaller than 0.05. Thus, there is an effect of the experimental method on student learning outcomes in IPAS lessons in the fourth grade at SD Negeri 1 Watubelah.